Persistent transmission of Plasmodium malariae and Plasmodium ovale species in an area of declining Plasmodium falciparum transmission in eastern Tanzania. - Victor Yman; Grace Wandell; Doreen D Mutemi; Aurelie Miglar; Muhammad Asghar; Ulf Hammar; Mattias Karlsson; Ingrid Lind; Cleis Nordfjell; Ingegerd Rooth; Billy Ngasala; Manijeh Vafa Homann; et al. (Public Library of Science (PLoS), 2019)
A reduction in the global burden of malaria over the past two decades has encouraged efforts for regional malaria elimination. Despite the need to target all Plasmodium species, current focus is mainly directed towards Plasmodium falciparum, and to a lesser extent P. vivax. There is a substantial lack of data on both global and local transmission patterns of the neglected malaria parasites P. malariae and P. ovale spp. We used a species-specific real-time PCR assay targeting the Plasmodium 18s rRNA gene to evaluate temporal trends in the prevalence of all human malaria parasites over a 22-year period in a rural village in Tanzania.We tested 2897 blood samples collected in five cross-sectional surveys conducted between 1994 and 2016. Infections with P. falciparum, P. malariae, and P. ovale spp. were detected throughout the study period, while P. vivax was not detected. Between 1994 and 2010, we found a more than 90% reduction in the odds of infection with all detected species. The odds of P. falciparum infection was further reduced in 2016, while the odds of P. malariae and P. ovale spp. infection increased 2- and 6-fold, respectively, compared to 2010. In 2016, non-falciparum species occurred more often as mono-infections. The results demonstrate the persistent transmission of P. ovale spp., and to a lesser extent P. malariae despite a continued decline in P. falciparum transmission. This illustrates that the transmission patterns of the non-falciparum species do not necessarily follow those of P. falciparum, stressing the need for attention towards non-falciparum malaria in Africa. Malaria elimination will require a better understanding of the epidemiology of P. malariae and P. ovale spp. and improved tools for monitoring the transmission of all Plasmodium species, with a particular focus towards identifying asymptomatic carriers of infection and designing appropriate interventions to enhance malaria control.